Effect of Farming System on Camels Calving Interval in Western Sudan - Sallam Abdelfadeil Bakheit; Bernard Faye; Adam Ismail Ahmed; Intisar Musa Elshafei (Turkish Journal of Agriculture: Food Science and Technology)
Eighteen (18) lactating she-camels and two mature male for mating were used to determine the effect of Management System on camel calving interval, The camels were maintained under semi-intensive (N = 9) and Traditional management system (N = 9) in North Kordofan State, western Sudan. The experimental females in each group kept together with the bull during 18 months. Blood samples were collected from jugular vein since 4-months post-partum and continue 14 successive months at monthly interval. The serum samples were separated and stored at -20°C and were analysed for progesterone concentration using progesterone specific radio immuno assay (RIA) kits. The results indicated that under semi-intensive system 77.8% of females had been pregnant in 5th - 8th month post-partum and the calving interval varying between 17 to 20 months. Under traditional system and during the experimental period 44.5% of females were pregnant in the 11th – 16th month and the calving interval varying between 23 to 28 months. The ratios of pregnant vs non-pregnant during experimental period in semi-intensive and traditional were 88.9% vs 11.1% and 44.5% vs 55.5%, respectively. Beside the behavioural signs progesterone level consider a good indicator for pregnancy in camels. In pregnant females Progesterone concentration increased significantly during early months. The range of Progesterone concentration varied between 1.10 – 5.76 ng/ml and 0.67 – 2.53 ng/ml in semi-intensive and traditional system, respectively. Our results allow quantifying this impact. With a supplemented diet including 2 Kg of concentrates and 5 kg of roughages per day, the fertility rate will be improved of 67%. It would be possible to expect more than two fold young camels in a year by supplemented 5 kg of concentrates. We conclude that under semi-intensive management dietary supplement during post-partum and early lactation period improves reproductive parameters for instance shortened calving interval.